Understanding meso-scale processes at a mixed-energy tidal inlet: Ameland Inlet, the Netherlands – Implications for coastal maintenance. (1st May 2022) - Elias, Edwin P.L.; Pearson, Stuart G.; van der Spek, Ad J.F.; Pluis, Stefan
Abstract: For successful and sustainable management of barrier islands, a thorough understanding of the ebb-tidal delta dynamics and interactions with the adjacent shorelines are of the utmost importance. Such understanding requires detailed observations and interpretations of the morphodynamics of smaller-scale features such as the individual channels and shoals (referred to as intra-delta dynamics). The intra-delta dynamics of Ameland Inlet (the Netherlands) are studied through analysis of sixteen high-resolution bathymetric surveys, supplemented with an extensive dataset of hydrodynamic observations collected in 2017. The observations are compiled into a synthesis of the morphodynamics of the ebb-tidal delta and its neighboring shorelines, to provide a basis for present day and future coastal management. Our observations show that Ameland Inlet as a whole can be classified as a typical mixed-energy, wave-dominated system. However, the ebb-tidal delta contains distinct areas that are wave or tide dominated, and these areas evolve with the changing morphodynamics of the ebb delta. Between 2005 and 2021, large morphodynamic changes have occurred on the ebb-tidal delta and continuous erosion of the island tips occurred. Limited wave-sheltering by the ebb-tidal delta exposes the shorelines of the adjacent barrier islands to significant wave-driven sand transports and sand losses. Sediment supply from longshore transport and the erosion of the updrift island Terschelling contributed to the formation, growth and migration of a series of ebb-chutes and lobes, which eventually led to complete relocation of the main channel on the ebb-tidal delta. This main channel relocation took 15 years to complete and is an example of the ebb-delta breaching model of sand bypassing. Changes in the sediment bypassing patterns result in a sediment starved western island tip of Ameland, necessitating repeated sand nourishments under the Dutch coastal maintenance policy. Our observations also confirm the role the ebb-tidal delta as a sand reservoir for the downdrift barrier island. The delta sand body is not a reservoir for the back-barrier basin, since the basin is predominantly supplied with sand eroded from the updrift island of Terschelling. As demonstrated in this study, the intra-delta dynamics of an ebb-tidal delta are complex and can change drastically through time. Only through detailed measurements and observations can all the intricate interactions that take place be unravelled. Highlights: Morphodynamics of Ameland Inlet ebb-tidal delta investigated based on extensive and detailed observations. Understanding the complex and variable intra-delta dynamics is essential for coastline management. Ebb-tidal delta breaching at Ameland Inlet occurs on a 15-year timescale. Limited wave-sheltering and sediment-bypassing variations induce island tip erosion.